ANALISIS EFESIENSI PENGGUNAAN PUPUK DAN PESTISIDA PADA USAHA TANI SEMANGKA DI KECAMATAN MUTIARA TIMUR KABUPATEN PIDIE - Mujiburrahmad Mujiburrahmad (Universitas Teuku Umar, 2017)
Farming is done by the aim to get high income and the amount of production cost is influenced by production factors such as seeds, fertilizer and labor. The Farmers can effectively cost production in the use of production factors. This research was conducted with the aim to knowing efficiency of Urea, SP-36, NPK and pesticide are used in watermelon farming. This study used survey methodwith cluster sampling sampling, sample size 50% of population (53 HH) or 27 HH. The data analysis method uses multiple linear regression production and efficiency test. The results showed that the ratio between the marginal product value (NPM) and urea fertilizer production factor was bigger than one (87.29), the SP-36 fertilizer was bigger than one (47,15), NPK fertilizer was bigger and one (79), pesticide was bigger than one (43,14) so that the use of fertilizer andpesticide production factor not yet efficient, the efforts to increase profits can be done by increasing the allocation of fertilizer and pesticide production factors in watermelon farming. Watermelon farmers can increase the use of inefficient production factors to increase unoptimized production